Rancang Bangun Sistem Informasi Reservasi Jasa Fotografi pada Lenstha Studio - Bayu Aji Sasmita; Muhammad Rahadian Dafa Saputra; Noviar Ilham Pratama (CV. Multi Kreasi Media, 2026)
Lenstha Studio is a photography service business whose reservation process is still carried out manually through WhatsApp and notebook records, causing repeated responses to customers and uncentered booking data storage. This study aims to design and develop a web-based photography reservation information system for Lenstha Studio to make the booking and customer data management process more efficient and well-documented. The development method used is the iterative Prototype method, while data collection was carried out through observation, interviews, and literature study. The system built includes studio information, service list, photo gallery, FAQ, online reservation form, QRIS payment, and management panels for admin and owner. Testing was carried out using black box testing on 12 test scenarios and all of them ran successfully as needed. The results show that the system helps customers make reservations independently, helps admins manage booking data and verify payments, and helps owners monitor financial and operational reports.